Synthesis of nano calcium oxide from cockle shells as stabilizer for fabrication of zirconia - Hussein, Abbas Ibrahim (2018)
Various studies suggest that cockle shells hold great potential as a rich source of natural calcium oxide (CaO). Different oxides have been used to stabilize zirconium oxide (ZrO2) in a stable phase. Use of CaO as a stabilizer has been studied previously; however, commercially prepared CaO has been utilized for these purposes. The aim of the current study was to derive CaO from cockle shell waste and to utilize cockle shell derived CaO for stabilizing ZrO2 and then to compare it with ZrO2 stabilized with commercial CaO. The physical and mechanical properties of the CaO stabilized zirconia derived from both sources were also investigated. CaCO3 samples were characterized using scanning electron microscopy, Brunaur-Emmett-Teller surface area analysis, X-ray diffraction analysis and energy dispersive X-ray analysis. The CaO was obtained through calcination process at a temperature range from 300-750 °C. Themorphology of CaCO3 were controlled by manipulation of reaction parameters such as DDW concentration, K2CO3 feeding rate, concentration of organic solvents, and the drying methods. The calcium oxide was used to stabilize zirconium sintering. (A) 9.2 g of commercially purchased zirconium oxide was mixed with 0.8 g of calcium oxide derived from cockle shells. (B) 9.2 g of commercially purchased zirconium oxide was mixed with 0.8 g of calcium oxide which was commercially purchased. Each specimen mixture was pressed in stainless steel mold using hydraulic press under 5 tons (60MPa) pressure and sintered for various times (one, two, three, and fourhours) at different temperatures (1200 °C, 1300 °C, 1400 °C, and 1500 °C) to fabricate pellets/blanks of CaO stabilized zirconia. SEM characterization of zirconia stabilizedusing cockle shells had an average particle size of 61.13 nm as compared to zirconia stabilized using commercial CaO that had an average particle size of 64.37 nm. It was noted that the nanoparticles had spherical shape and they were evenly distributed with no visible agglomeration. EDX composition analysis revealed that percentage of zirconia was higher in zirconia stabilized using nano CaO derived from cockle shells in comparison to zirconia stabilized using commercial nano CaO. XRD analysis revealed that the highest peak for the nano CaO stabilized zirconia crystals in the XRD pattern was noted at an angle 2θ=30° depicting spherical crystals of zirconia. Flexural strength test, compressive strength test, Vickers hardness test and density test were performed for each sample. These tests concluded that nano CaO stabilized zirconia from cockle shell is comparable to zirconia stabilized by commercial nano CaO and had superior mechanical and physical properties when sintered at 1400 °C for 2 hours holding time. It can be concluded from our study that the cockle shell waste is a rich source of nano CaO. Mechanical and physical tests prove that nano CaO stabilized zirconia derived from cockle shell can be considered suitable for dental applications.